Analysis of the Dominant Mode of Convectively Coupled Kelvin Waves in the West African Monsoon - (:unkn) unknown (My University, 2007)
The dominant mode of convectively coupled Kelvin waves has been detected over the Atlantic and Africa during northern summer by performing composite analyses on observational fields based on an EOF reconstructed convection index over West Africa. Propagating eastward, many waves originate from the Pacific sector, interact with deep convection of the marine ITCZ over the Atlantic and the continental ITCZ over West and central Africa, and then weaken over East Africa and the Indian Ocean. It has been shown that they are able to modulate the life cycle and track of individual westward-propagating convective systems. Their mean kinematic characteristics comprise a wavelength of 8000 km, and a phase speed of 15 m s−1, leading to a period centered on 6 to 7 days. The African Kelvin wave activity displays large seasonal variability, being highest outside of northern summer when the ITCZ is close to the equator, facilitating the interactions between convection and these equatorially trapped waves. The convective and dynamical patterns identified over the Atlantic and Africa show some resemblance to the theoretical equatorially trapped Kelvin wave solution on an equatorial β plane. Most of the flow is in the zonal direction as predicted by theory, and there is a tendency for the dynamical fields to be symmetric about the equator, even though the ITCZ is concentrated well north of the equator at the full development of the African monsoon. In the upper troposphere and the stratosphere, the temperature contours slope sharply eastward with height, as expected from an eastward-moving heat source that forces a dry Kelvin wave response. It is finally shown that the mean impact of African Kelvin waves on rainfall and convection is of the same level as African easterly waves.
Keywords: African Research